The Impact Of Digital Marketing Strategies On Mortgage Products To Increase The Number Of Customers At Bank Tabungan Negara Semarang Branch Office - Akhva Dhani Dwi Tama; Raden Roro Ratna Roostika (UNIVED Press, 2025)
One of the basic human needs that is very important for human life is a house, which makes it one of the priorities in social development. Therefore, Home Ownership Credit (KPR) becomes a solution that allows the community to easily own a house. This research aims to determine the effectiveness of digital marketing on subsidized and non-subsidized mortgage products in increasing customers at PT Bank Tabungan Negara (BTN) Kc Semarang. This research uses a qualitative method. For the research data sources, it employs primary and secondary data obtained through interviews, observations, documentation, internet searching, books, and journals. The results of this study indicate that digital marketing for mortgage products is very effective in increasing customers.